A study of copolymers activity during the separation of water-in-oil emulsions. (1st February 2017) - Sánchez-Minero, Felipe; Marroquín, Gustavo; Ortiz-Moreno, Hugo; Avendaño-Gómez, Juan
ABSTRACT: The activity of copolymers poly (propylene oxide)-poly (ethylene oxide) (PPO-PEO) with different amount of PEO (10 and 15 wt%) was studied on the separation of water from water-in-oil (W/O) emulsions. The results show an increase in the interfacial activity of the copolymer when PEO concentration was 15 wt%. However, the increase in molecular size of the copolymer due to high concentration of PEO may cause problems related to transport through the emulsion. Thus, while the PPO-PEO10 copolymer was more active for the separation of water present in the W/O emulsion of 6.4° API, which is highly viscous, the PPO-PEO15 copolymer was more effective for the W/O emulsion of 7.1° API, which is highly stable.